Direct and indirect effects of economic sanctions on health: a systematic narrative literature review - Vahid Yazdi-Feyzabadi; Atefeh Zolfagharnasab; Soheila Naghavi; Anahita Behzadi; Maysam Yousefi; Mohammad Bazyar (BMC, 2024)
Abstract Background Economic sanctions are defined as restrictions imposed by other countries against individuals, groups, or governments of other countries. These sanctions have a detrimental impact on the economies of countries and can also limit access to healthcare services for people as a secondary consequence. This study aims to systematically review the literature to examine the direct and indirect effects of economic sanctions on health through a narrative synthesis. Methods This systematic literature review was limited to papers published between January 1990 and July 2023. Relevant documents published in English and Persian were searched for in databases including Cochrane Library, PubMed, Embase, Scopus, Web of Science, SID, Magiran, and Irandoc. The direct and indirect effects of sanctions on health were classified using two frameworks proposed by the World Health Organization (WHO): the Health System Building Blocks and "Social Determinants of Health". Results Out of a total of 18,219 articles, 59 were selected based on inclusion criteria. The effects of sanctions were divided into direct and indirect groups. Direct effects encompassed seven main themes: access to essential medicine, medical products, vaccines and technologies; financing; health workforce; service delivery; research and health information systems; health outcomes; and financial risk protection. Indirect effects also were classified into six main themes: socioeconomic status; food and agricultural products; stress; early life conditions; high-risk behaviors and addiction; and transport. Most studies focused on the access to medicines, food, economic and social status. Conclusions Economic sanctions have had profoundly negative impacts on all aspects of the healthcare system. The international community must address these effects on health and take necessary measures to prevent or mitigate them, particularly in ensuring the provision of basic and essential healthcare needs for individuals and communities.